Increased functional connectivity within medial temporal lobe in mild cognitive impairment. Issue 1 (20th July 2012) - Das, Sandhitsu R.; Pluta, John; Mancuso, Lauren; Kliot, Dasha; Orozco, Sylvia; Dickerson, Bradford C.; Yushkevich, Paul A.; Wolk, David A.
Abstract Pathology at preclinical and prodromal stages of Alzheimer's disease (AD) may manifest itself as measurable functional change in neuronal networks earlier than detectable structural change. Functional connectivity as measured using resting‐state functional magnetic resonance imaging has emerged as a useful tool for studying disease effects on baseline states of neuronal networks. In this study, we use high resolution MRI to label subregions within the medial temporal lobe (MTL), a site of early pathology in AD, and report an increase in functional connectivity in amnestic mild cognitive impairment between entorhinal cortex and subregions of the MTL, with the strongest effect in the anterior hippocampus. However, our data also replicated the effects of decreased connectivity of the MTL to other nodes of the default mode network reported by other researchers. This dissociation of changes in functional connectivity within the MTL versus the MTL's connection with other neocortical structures can help enrich the characterization of early stages of disease progression in AD. © 2012 Wiley Periodicals, Inc.